A Study on the Stochastic Approximation Method during the Single Server Queueing System with Catastrophe - Reni Sagayaraj, M.; Anand Gnana Selvam, S.; Manoharan, P.; Reynald Susainathan, R. (Asian Journal of Science and Applied Technology, 2016)
We consider an M/G/1 queueing system where the customer arrivals occur according to a Poisson process with mean arrival rate λ. The server is subject to catastrophe and repairs while in operation. At failure times, the server still works at a lower service rate rather than completely stopping service.The service time follow general laws with probability distribution function and Laplace Stieltjes transform. Using the approximation conditions in the classical M/G/1 system, we obtain stability inequalities with exact computation of the constants.